"So what happens next?" exploring the psychological and emotional impact of anti-Mullerian hormone testing. (2nd January 2020) - O'Brien, Yvonne; Kelleher, Caroline; Wingfield, Mary
Abstract: Research Question : Significant medical benefits could be derived from universal AMH screening for women in their mid to late twenties. We aimed to investigate the psychological and emotional responses of women to being informed of their anti-Mullerian hormone (AMH) result with a view to informing the possible introduction of universal AMH screening. Materials and methods : This was a prospective qualitative study using semi-structured in-depth interviews of women attending a reproductive medicine clinic who had ovarian reserve testing performed via measurement of serum AMH levels, as part of their gynecological investigations. A semistructured interview schedule was developed after a review of the literature. A purposive sample of women was recruited, and data collection continued until thematic saturation was reached ( n  = 10). The number of women interviewed is low as this was a pilot qualitative study of a two-part study. The next part of the study involves the development of a quantitative questionnaire related to the key themes identified in this study to be based on a much larger group of women. Interviews were audiotaped, transcribed verbatim and imported into QSR NVivo pro 11 for analysis. Results: Three key themes emerged from the data: the experience of AMH testing, the response to the AMH result, and suggested lessons for medical professionals. The theme of the experience of AMH testing describes and reflects two sub-themes: the reasons for ovarian reserve testing and the potential barriers that may prevent women from accessing testing. A further key focus of this study was the emotional and psychological responses to receiving an AMH result and this emerged as a major theme in the interviews. Women described the significant impact that their individual result had on a number of lifestyle and behavioral factors and how it impacted on their gender identity. Lessons for medical professionals including the appreciation of the patient's awareness of the test and how the test result was relayed to the patient were important factors in how they dealt with the result. There were mixed reactions and opinions from the group in relation to the introduction of AMH testing as a screening tool for all young women. Conclusions: Knowledge and communication of a low AMH result has a negative psychological impact. The findings from this study support the move to further explore the psychological and emotional impact of the test with the development of a quantitative questionnaire.